The Elevated Expressions of Anti-lipopolysaccharide Factors After Priming Stimulation Confer Lastingly Humoral Protection in Crab Eriocheir sinensis - Wang, Weilin; Li, Yan; Fan, Siqi; Lian, Xingye; Cao, Wanqing; Song, Xiaorui; Yi, Qilin; Wang, Lingling; Song, Linsheng (Frontiers in Immunology, 2021)
Evidence of immune memory in invertebrates (immune priming) has accumulated in various organisms, and both cellular and humoral immune reactions are speculated to be involved in immune priming. However, there is a lack of understanding of the molecular mechanisms involved. In the present study, the protective effect of primed haemolymph was further validated by the increased survival rate of naïve crabs receiving a transfusion of primed haemolymph. By proteomic analysis, there were 474 proteins identified from the primed haemolymph, and most of them were functionally annotated in transport and metabolism classes. A total of 70 proteins were found to be differentially expressed in haemolymph at 12 hours and 7 days after priming stimulation with Aeromonas hydrophila, among which anti-lipopolysaccharide factor 1 (EsALF-1) and 3 (EsALF-3) were identified as the most significant (p < 0.05). After being challenged with A. hydrophila, EsALF-1 and EsALF-3 were highly expressed at both mRNA (in haemocytes) and protein (in haemolymph) levels compared with blank crabs, and the mRNA expressions of components in the EsTLR1-EsMyd88-EsPelle-EsALF pathway also increased significantly (p < 0.05). The EsALF-3 and EsMyd88 were even significantly higher expressed in response to the second A. hydrophila challenge, but their expressions all decreased (p < 0.05) when EsTLR1 was knocked down by RNAi. After the naïve crabs received an injection with the recombinant protein of EsALF-1 (rEsALF-1) or EsALF-3 (rEsALF-3), their survival rate increased significantly (p < 0.05) upon A. hydrophila stimulation. In contrast, the survival rate of the primed crabs reduced significantly (p < 0.05) after they received an injection with the antibody of EsALF-1 or EsALF-3. The enhanced expressions of EsALF-1 and EsALF-3 after A. hydrophilap riming stimulation could sustain for four weeks. All the results suggested that the EsTLR1-mediated productions of EsALF-1 and EsALF-3 in haemolymph played an indispensable role in the month-long humoral immune protection induced by A. hydrophila, which provides solid evidence of immune priming in crabs and a valuable reference for further understanding immune memory in invertebrates.